Accounting information in improving corporate values and responsibility to stakeholders in cement manufacturing companies in Indonesia - Ali Hardana; Try Wahyu Utami; Lismawati Hasibuan; Windari (Junal Ilmu Manajemen, 2023)
The study looked at manufacturing cement as an object of research. Reasons why the cement industry go the public is: 1). Manufacturing companies Cement is still very little that goes public in Indonesian; 2). Cost of goods calculation production at more manufacturing companies complex when compared to service companies. The purpose of this study is to determine the effect of cost accounting information on the improvement of corporate value and responsibility to stakeholders, in the cement industry companies listed in Indonesia Stock Exchange (BEI) period 2017-2022. Data analysis techniques using simple linear regression analysis product correlation moment for causality test and comparative analysis k one way ANOVA independent sample for comparative test, with 5% significance level. The results showed that the cost accounting information, which is realized in the calculation of cost of goods manufactured significantly affects the increase of company value. Increased corporate value significantly influences the company's ability to fulfill its responsibilities to stakeholders, such as paying dividends to shareholders, borrowing interest expenses to creditors, hiring employees, and paying taxes to the government. This study also concludes that there are differences in firm size, dividend payout, tax burden, interest expense on cement the company goes public in Indonesia, while the salary load is not significantly different.